Revealing the Ideology of Documentary Film Dirty Vote: Critical Discourse Analysis with Transitivity Perspective - Wulansari, Atsani; Mazid, Sukron (Universitas Tidar, 2024)
The Dirty Vote documentary movie attempted to depict the ambiance of Indonesia’s general election. Movies inherently reflect the viewpoints and ideology of particular groups; therefore, it led us to research the film further by using Critical Discourse Analysis. Film as one of the discourses has its linguistics characteristic which brings the ideological orientations. This research aims to reveal the ideology of Dirty Vote from transitivity perspective. Transitivity is the ideational function that can show what happens in a text as it is related to a series of context in which participants, processes, and circumstance must be used in a discourse. In addition, this research uses Fairclough›s Critical Discourse Analysis to reveal ideological assumptions in discourse. The data is taken from the utterance of one of the constitutional law experts, namely Zainal Arifin Mochtar (ZAM). Fairclough›s CDA model: description, interpretation and explanation are used to analyze the data. This study found that the processes in opening of the film are relational attributive process, material process and behavioral process. Meanwhile, the processes perceived in the content of the movie are material, relational attributive, relational identifying, behavioral, verbal, mental, and existential process. The transitivity analysis in the film produces representation of general election reflected in the ZAM’s speech and create the ideology of the film.